1995
DOI: 10.1152/ajplung.1995.268.6.l894
|View full text |Cite
|
Sign up to set email alerts
|

Role of MAP kinase activation in bovine tracheal smooth muscle mitogenesis

Abstract: Abnormal growth of airway smooth muscle may play an important role in the pathogenesis of human airway diseases. Little is known about the proliferative responses of cultured airway smooth muscle cells, nor of the precise pathways responsible for mitogenesis in these cells. We assessed DNA synthesis, cell proliferation, and mitogen-activated protein (MAP) kinase activation in bovine tracheal myocytes after exposure to four potential mitogens: platelet-derived growth factor (PDGF), epidermal growth factor (EGF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 0 publications
8
52
0
Order By: Relevance
“…However, no effect of salbutamol was found on cyclin D 1 mRNA, suggesting a post-transcriptional effect on cyclin D 1 , perhaps involving accelerated degradation of the cyclin D 1 protein [159]. In contrast to the lack of effect of glucocorticoids on ERK activity [155], salbutamol prevented ERK activation between 5 min and 8 h following stimulation with a-thrombin, consistent with earlier reports that sustained ERK activation throughout G 1 is necessary for cell cycle traversal [74,75,78]. An additional mechanism that was not investigated in this study, but has been reported previously by these authors [160], was the salbutamol-induced expression of p27 kip1 , a cdk protein inhibitor which prevents phosphorylation of pRb and cell cycle progression by inhibiting cdk activity in the mitogen-activated cyclin D 1 /cdk4 complex.…”
Section: Role Of Phosphoinositide 3-kinase Activation In Proliferationsupporting
confidence: 88%
See 4 more Smart Citations
“…However, no effect of salbutamol was found on cyclin D 1 mRNA, suggesting a post-transcriptional effect on cyclin D 1 , perhaps involving accelerated degradation of the cyclin D 1 protein [159]. In contrast to the lack of effect of glucocorticoids on ERK activity [155], salbutamol prevented ERK activation between 5 min and 8 h following stimulation with a-thrombin, consistent with earlier reports that sustained ERK activation throughout G 1 is necessary for cell cycle traversal [74,75,78]. An additional mechanism that was not investigated in this study, but has been reported previously by these authors [160], was the salbutamol-induced expression of p27 kip1 , a cdk protein inhibitor which prevents phosphorylation of pRb and cell cycle progression by inhibiting cdk activity in the mitogen-activated cyclin D 1 /cdk4 complex.…”
Section: Role Of Phosphoinositide 3-kinase Activation In Proliferationsupporting
confidence: 88%
“…Interestingly, S-phase entry and proliferation, as determined by BrdU labelling or 3 H-thymidine incorporation, could not be induced in these cells by hydrogen peroxide [79]. This may reflect a requirement for sustained ERK activation in proliferation [74,75,78], or that activation of the p38MAPK or SAPK/JNK pathway by hydrogen peroxide in these cells [79] may in some way counter the effect of ERK activation.…”
Section: Mediators Of Airway Smooth Muscle Proliferationmentioning
confidence: 87%
See 3 more Smart Citations